Penerapan Steganografi Pada Image GIF Menggunakan Metode Ezstego dan Elgamal - Fattah, Mhd Ariya (Forum Kerjasama Pendidikan Tinggi (FKPT), 2020)
Security and data confidentiality is one of the important aspects in terms of information exchange. One of the solutions to maintain the security and confidentiality of the steganography process is the message insertion technique for file encryption with electronic cryptography used for Gif image steganography. This study describes the development of steganography that applies the Ezstego algorithm which is used for Gif image steganography. The ezstego algorithm was chosen because it inserts message bits from pixel values. This research produces an application program that aims to prevent safety on Gif images. Gif image is a type of indexed image, the jif format is usually used to store computer graphic images, iconic images, cartoons, logos, animation and natural images. In making this application, the method used is the Eztego Algorithm, because it is very suitable for Gif image steganography which results in the completion of the electronic cryptography process on message insertion. This application is made with Visual Basic 2008 software and the creation of a Gif image steganography application with the process of inserting an encryption message and description is expected to solve this problem.